7‐2: High Transmittance Under‐Display Camera Structure with COE. Issue 1 (28th June 2022) - Xu, Chuan X.; Yao, Qi; Li, Xiao H.; Shu, Shi; He, Wei; Xu, Zhi Q.; Dong, Li W.; Wang, Wei J.; Gao, Zhi K.; Yuan, Guang C.
Abstract : A novel under‐display camera structure with high transmittance up to 40.8% was proposed to increace transmittance, in which all pixel circuits and metal traces were moved to the transition zone which is right next to the UDC zone, and the circular polarizer was replaced with COE, and then the metal cathode is patterned by self‐assembly method, and the disconnected cathodes are connected together by transparent auxiliary cathode.